Structural analysis of cumulus and corona cells of goat antral follicles: Possible functional significance - SHARMA, R K (The Indian Journal of Animal Sciences, 2014)
Ultrastructural analysis of cumulus and corona radiata cells obtained from medium antral follicles (MAE 2-5mm) and large antral follicles (LAF >5mm in diameter) was made during the follicular phase of ovarian cycle in goat (Capra hircus). The fine structure of 2 cell populations showed changes in size, shape and number of cell organelles with changing follicle size. The mitochondria, Golgi complex, rough endoplasmic reticulum, smooth endoplasmic reticulum, lipid droplets, and glycogen bodies showed a change in their relative abundance and distribution. The qualitative analysis of cell organelles and their relative percentile in total cytoplasm showed variations not only between cumulus and corona cells but also in 2 stages of follicle development. The hormonal profile and synthetic activity of these cells were analyzed to explore their physiology.